Exclusion of autosomal recessive hereditary spastic paraplegia loci in Turkish families - Özeş, Burçak. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Hereditary spastic paraplegias (HSPs), also known as Strümpell-Lorrain disease, describe a heterogeneous group of genetic neurodegenerative disorders. The main feature of the disease is progressive spasticity in the lower limbs. HSPs are classified according to the mode of inheritance, which can be autosomal dominant, recessive, or X-linked. In this study, 15 families with possible autosomal recessive inheritance were analyzed and linkage to AR-HSP loci -SPG5, SPG7, SPG11, SPG15, SPG20 and SPG21- was tested. The genes responsible for the disease have already been identified in these loci. SNP markers that are located on restriction sites were used for haplotype analysis. For one family, linkage to SPG11 and for another family, linkage to SPG15 was observed. In four of the families, linkage to all tested loci was excluded. Among the other ten families analyzed, in four families SNP markers on SPG5, SPG11, or SPG21 were non-informative since both affected and unaffected individuals were homozygous for one of these loci. SPG7 locus markers gave inconclusive results in five families, just as markers in SPG20 locus giving inconclusive results for one family. In two of the families, restriction analyses gave both non-informative and inconclusive results. Patients in two of the families analyzed in this study were found to be homozygous for markers in SPG11 locus. Other loci were excluded in these ten families. Higher incidence of autosomal recessive types of HSP in the Turkish population with respect to western countries provides a gateway for the identification of causative genes. Since known genes are excluded in the majority of our families, the causative mutations are localized either to unknown loci or to other loci for which the responsible gene has not been identified, yet. Therefore, this study forms a base for future studies that will possibly lead to identification of novel genes.
Keywords: Genetic disorders -- Turkey.; Central nervous system -- Diseases -- Turkey.